Greater numbers and sizes of muscle bundles in the breast and leg muscles of broilers compared to layer chickens - Lee, Boin; Kim, Dong-Hwan; Lee, Joonbum; Cressman, Michael D.; Choi, Young Min; Lee, Kichoon (Frontiers in Physiology, 2023)
Meat-type (broiler) and egg-type (layer) chickens were bred by intensive selection over the years, resulting in more numbers and larger sizes of myofibers. Although the characteristics are important parameters in muscle growth and meat quality, muscle bundle characteristics have not been studied in poultry. Therefore, this study aimed to compare the histological characteristics of myofibers and muscle bundles in muscles between male broiler (Ross broiler breed) chickens and layer (Hy-Line) chickens. Chicken muscles, pectoralis major (PM) and gastrocnemius (GM), were sampled at the age of 49 days and stained to analyze histological characteristics. Expectedly, body weights (BWs) and weights of PM and GM muscles in 49-day-old broilers were significantly heavier than those in layers. Within PM, broilers exhibited greater number and cross-sectional area (CSA) of myofibers than layers (3.3- and 3.3-fold, respectively). The total number and CSA of PM muscle bundles were approximately 1.5 and 6.6 times greater, respectively, in broilers than layers. Moreover, broilers exhibited 2 times greater number of myofibers per bundle of PM muscle than layers. Within GM, myofiber number and CSA were 2.3- and 2.4-fold greater, respectively, in broilers than layers. In addition, the total number of muscle bundles and bundle CSA were 2.5- and 2.1-fold greater, respectively, in broilers than in the layers. The novel findings of the current study provide evidence that greater muscle mass of broilers occurs by both hyperplasia and hypertrophy of muscle bundles and myofibers.